2014
DOI: 10.1210/jc.2013-2298
|View full text |Cite
|
Sign up to set email alerts
|

The VEGF Inhibitor Axitinib Has Limited Effectiveness as a Therapy for Adrenocortical Cancer

Abstract: Axitinib has limited effectiveness in ACC. Together with 48 patients previously reported who received either sorafenib or sunitinib, a total of 61 ACC patients have now been treated with a VEGFR tyrosine kinase inhibitor without an objective Response Evaluation Criteria in Solid Tumors response. Future trials in ACC should look to other targets for possible active agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…Two phase 2 trials analyzed the antitumor response to sunitinib or axitinib and reported no PR and median PFS of 83 days or 5 months in 35 or 13 pretreated patients with ACC, respectively. 90,115 In 2 additional phase 2 trials, combination of antiangiogenic agents with chemotherapy was investigated. In 1 study, bevacizumab plus capecitabine in 10 pretreated patients with ACC produced no PR and median PFS was 59 days.…”
Section: Molecular Targeted Therapiesmentioning
confidence: 99%
“…Two phase 2 trials analyzed the antitumor response to sunitinib or axitinib and reported no PR and median PFS of 83 days or 5 months in 35 or 13 pretreated patients with ACC, respectively. 90,115 In 2 additional phase 2 trials, combination of antiangiogenic agents with chemotherapy was investigated. In 1 study, bevacizumab plus capecitabine in 10 pretreated patients with ACC produced no PR and median PFS was 59 days.…”
Section: Molecular Targeted Therapiesmentioning
confidence: 99%
“…Several studies have been undertaken with VEGFR inhibitors in patients with ACC (Table 5). Three phase II studies evaluated sorafenib in combination with paclitaxel, sunitinib or axitinib respectively , Kroiss et al 2012, O'Sullivan et al 2014). Sorafenib did not show an anti-tumor effect in patients, whereas sunitinib and axitinib showed a partial response in 14 and 62% of the patients respectively (Table 5).…”
Section: Future Directions and Pathway Driven Therapiesmentioning
confidence: 99%
“…Targeting of tumor vasculature has also attracted attention in ACC treatment as we and others have detected high expression of vascular endothelial growth factor (VEGF (VEGFA)) and its receptor VEGFR2 (KDR) in many ACC specimens (43,70,71,72). Among the VEGFtargeting drugs (58,73,74,75), the multi-TKI sunitinib has demonstrated modest anti-tumor effects in a phase II clinical trial. Of the 35 patients analyzed per protocol, five patients (14%) experienced stable disease, but no objective tumor response was observed (58).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%